Toward a Non-Nuclear World: The NPT Regime – Nuclear Disarmament and the Challenge of a WMDFZ in the Middle East - Sameh Aboul-Enein (International Journal of Nuclear Security, 2017)
This paper aims to provide a comprehensive overview of various approaches for nuclear disarmament and nonproliferation with the intention of determining how best to promote a Weapons of Mass Destruction Free Zone in the Middle East (MEWMDFZ). Using a qualitative approach, I investigate historical cases of agreements regarding nonproliferation zones and examine the causes for deadlock through both a perusal of historic successes and failures and a review of relevant literature. Particular focus is given to the failure of the NPT Review Conference of 2015. Furthermore, I discuss the importance of role-play simulations and their indications of the need for capacity-building and for cooperation on verification, dismantlement, and security assurances. The paper concludes that empowering and institutionalizing the NPT Review Process is necessary for the establishment of an MEWMDFZ and that concrete steps must be taken toward dismantling existing programs and disarming existing nuclear powers in order to move forward in the zonal process. I argue that an extensive verification scheme, in which nuclear-weapon states make an annual declaration to a register maintained by the United Nations, would promote transparency and enhance confidence in the arms reduction process.